Autonomous inspection and repair of aircraft composite structures - Kostopoulos, Vassilis; Psarras, Spyridon; Loutas, Theodoros; Sotiriadis, George; Gray, Iain; Padiyar M, Janardhan; Petrunin, Ivan; Raposo Gaudencio Campos, Joao; Zanotti Fragonara, Luca; Tzitzilonis, Vasileios; Dassios, Konstantinos; Exarchos, Dimitrios; et al. (Elsevier, 2018)
This paper deals with the development of an innovative approach for inspection and repair of damage in aeronautical composites that took place in the first two years of the H2020 CompInnova project which. The aim is a newly designed robotic platform for autonomous inspection using combined infrared thermography (IRT) and phased array (PA) non-destructive investigation for damage detection and characterization, while integrated with laser repair capabilities. This will affect the increasing societal need for safer aircraft in the lowest possible cost, while new and effective techniques of inspection are needed because of the rapidly expanding use of composites in the aerospace industry.
Keywords: Composites; Repairs; Laser; Autonomous inspections; Vortex robot